Confocal Laser Endomicroscopy in the Study of Colonic Mucosa in IBD Patients: A Review - Francesca Salvatori; Saverio Siciliano; Francesco Maione; Dario Esposito; Stefania Masone; Marcello Persico; Giovanni D. De Palma (Gastroenterology Research and Practice)
Confocal laser endomicroscopy (CLE) is one of several novel methods that provide real-time, high-resolution imaging at a micronscale via endoscopes. CLE and related technologies are often termed “virtual biopsy” as they simulate the images seen in traditional histology. Recently, the use of CLE was reported in the study of colonic mucosa in patients with inflammatory bowel diseases and in particular in patients affected by ulcerative colitis. CLE has the potential to have an important role in management of IBD patients as it can be used to assess the grading of colitis and in detection of microscopic colitis in endoscopically silent segments. Moreover, CLE can be used in surveillance programs especially in high-risk patients. This report aims to evaluate the current data on the application of confocal endomicroscopy in clinical gastroenterology and particularly in the study of colonic mucosa in UC patients.